Experimental micro-mechanics of granular media studied by x-ray tomography: recent results and challenges. Issue 3 (23rd July 2013) - Viggiani, G.; Hall, S. A.; Desrues, J.; Andò, E.
Abstract : Combining x-ray tomography and three-dimensional (3D) image analysis has finally opened the way for experimental micro-(geo)mechanics, allowing access to different scales of interest. When these correspond to a scale that has been imaged at high spatial resolution, high-quality measurements can be obtained (e.g. 3D displacements and rotations of individual grains of sand sample under load). However, there are issues when the scale of interest is smaller, for example the characterisation of grain-to-grain contacts (their orientations and evolution) or production of fines by grain breakage. This paper presents a short selection of new grain-scale measurements obtained using existing techniques. The challenges associated with smaller scale measurements on the same images are also discussed through a few examples from ongoing work.